Venture vs Investment, Which Type of Financing was more Demanded by Agriculture, Forestry, and Aquaculture Sector? - Achmad Nur Iman; Akhmad Kusuma Wardhana; Sulistya Rusgianto; Ririn Tri Ratnasari (PT Mattawang Mediatama Solution, 2022)
COVID-19 creates uncertainty on business. SMEs in Indonesia need to take a loan to survive. Sharia banks could give credit financing based on Islamic law. This study has a purpose to observe if the total value of credit financing issued by sharia bank in Indonesia affects the total financing of agriculture, forestry, and aquaculture sectors. This study uses secondary data taken from ojk.co.id as the sample. The independent variable is credit financing use for capital venture and investment. Dependent variables are the total financing in the agricultural, forestry, and aquaculture sectors. Data is analyzed using the linear regression method. The data of each variable was also tested using a T-test to analyze if there were significant changes during the COVID-19 pandemic. Result showed that financing of capital venture has a moderate impact on the total of credit financing for agriculture and forestry sector, while investment is none. Moreover, the COVID-19 pandemic has no effect in changing the number of credits issued by sharia banks nor credit received by agriculture, forestry, and aquaculture sectors. Sharia bank implemented two pillars of maqashid, which are the protection of life and wealth in issuing credit financing. The total of credit issued by sharia banks in Indonesia affected Agriculture & forestry sectors for capital, but not for investment. Sharia bank implemented two pillars of maqashid, which are the protection of life and wealth in issuing credit financing